New Avenues for Marketing of Library and Information Services and Products: A Study of Management Libraries of NCR - Gaur, Ramesh C. (Journal of Information and Knowledge, 2002)
In this paper efforts have been made to find out new ways and means for the marketing of library information services and products through a survey carried out in the 13 management libraries of National Capital Region (NCR) of Delhi. Issues involved in the marketing of library and information services have been discussed. On the basis of the findings of the survey the new ilvenues availab1e in the above field has been presented.